Підвищення надійності кіл опалення електровозів ЧС4 та ЧС8 - Маренич, Олександра Олександрівна (НТУ "ХПИ", 2011)
Визначено струми плавлення силових контактів для контакторів 7SP1 та 1SVAD8 у колі опалення електровозів ЧС4 та ЧС8. Показані випадки, коли струми КЗ значно перевищують струми плавлення. Розроблені рекомендації щодо значення струму термічної стійкості для апаратів у колах опалення

Power contact fusing currents for 7SP1 and 1SVAD8 contactors used in heating circuits of electric locomotives have been determined. It has been shown that in operation there may be situations when short-circuit currents are significantly greater than fusing currents. In this condition, a short-circuit current goes through the contactors contacts before protection actuation over a period of time long enough for the contacts fusion resulted from insufficient thermal stability current. Recommendations for thermal stability current values in the heating circuits have been developed
Improvement of heating circuit reliability in CHS 4 and CHS8 electric locomotives
Keywords: струми КЗ; струми плавлення; трансформатор; електрообладнання; heating circuits; electric locomotives; short-circuit; power contacts